Motivasi Peningkatan Pendidikan FormaI Pegawai Dan Kebijakan Organisasi Terhadap Pengembangan Sumber Daya Manusia Pada Bea Cukai Kediri - Achmad, Okziyar Hadafi; Talkah, Abu; Jatmiko, Anang Rohmad; Askafi, Eka (Otonomi, 2025)
Formal education is structured education provided by official institutions such as schools and universities. In addition to obtaining degrees, formal education also aids in personal development, critical thinking, and shaping individual character. For Civil State Apparatus (ASN/Aparatur Sipil Negara), advancing formal education is essential for self-improvement, career growth, and adapting to the changing times. Motivation and interest are key factors in an ASN's decision to pursue further education. Government policy support through various regulations encourages ASN to enhance their competencies. The objective of this research is to examine the influence of employees' motivation to advance formal education and organizational policies on human resource development at KPPBC TMC Kediri. The method used in this study is a quantitative approach, with data collection conducted through questionnaires and data processing using SPSS.